2022
DOI: 10.1007/s10639-022-11008-5
|View full text |Cite
|
Sign up to set email alerts
|

Distance Education among Italian Teachers: Differences and Experiences

Abstract: The successful integration of technology in teaching is a key component of education. Although prior research highlighted factors fostering the use of technology by teachers, few studies focused on whether these factors vary among teachers of different grade levels and subjects. Moreover, no studies have investigated personal experiences related to distance education among a large sample of teachers. To address these gaps, the present mixed-method study sought to examine whether factors promoting distance educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 117 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…In contrast, for novice teachers, this sudden transition might not have had the same impact on the assessment of their self-efficacy because they had not yet consolidated their daily teaching routines and experiences. Furthermore, many pre-service teachers may be part of the "net generation" that already actively use technology in everyday living [28].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for novice teachers, this sudden transition might not have had the same impact on the assessment of their self-efficacy because they had not yet consolidated their daily teaching routines and experiences. Furthermore, many pre-service teachers may be part of the "net generation" that already actively use technology in everyday living [28].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these difficulties, teachers appeared to recognize the importance technology use in their educational practices. In fact, in their studies on teachers' positive acceptance of technology in online classrooms, Menabò et al (2022) found that Italian teachers praised technology as an opportunity to develop digital skills and create versatile lessons. Further evidence emerged from the outcomes linked to the widespread implementation of technology in educational practices, as teachers positively judged their abilities to provide personalized educational material, quickly adapt to online-only educational environments and effectively apply their pedagogical readiness to remote education.…”
Section: The Italian Contextmentioning
confidence: 99%
“…A solution to these needs is raising teachers' awareness of the ease of digital tool use, since the likelihood of technology adoption is highly dependent on teachers' efficacy to manage and implement these resources. In fact, as demonstrated by research conducted by Menabò et al (2022) on Italian school teachers, online teaching strongly affects the relationship between perceived usefulness and ease of use of technology. This stresses the importance of encouraging teachers to use technologies that can easily be integrated in classroom activities so that teachers' efficacy can be promoted to high levels.…”
Section: The Italian Contextmentioning
confidence: 99%
“…A significant challenge that has emerged in the international literature concerns educators' limited skills in the use of digital technologies to support ERT. Teachers reported not being ready for the distance education process, expressing the need for training and support for them to be able to design and provide meaningful but socially distant learning experiences [15][16][17][18][19][20]. Students' limited technical skills and inequitable access to digital devices and the internet were also major barriers reported by teachers internationally [8,9,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Teachers also reported difficulties due to non-reliable internet access and/or a lack of infrastructure [20]. However, despite their difficulties in shifting from face-to-face teaching to ERT, educators not only highlighted challenges but also identified positive aspects and opportunities emerging from the pandemic [11,23], such as the possibility to interact with students even in a period of emergency [17], to create meaningful and engaging lessons using innovative technologies [17][18][19]24], and to foster students' digital literacy skills and other key 21st century competences that were previously difficult to cultivate [2].…”
Section: Introductionmentioning
confidence: 99%